Prevalence of Musculoskeletal Discomfort in Bank Employees - Kotwani, Shweta Kotwani; Sinha, Nikita; Panhale, Vrushali (International Journal of Innovative Research in Medical Science, 2019)
Keywords: bank employees, musculoskeletal discomfort, Nordic questionnaire, VAS, prevalence, work related musculoskeletal disorders, repetitive injuries.